Sociodemographic, lifestyle, and psychological factors as controllable predictors of academic self-efficacy after reforming a medical education system; the Egyptian Nationwide experience - Ahmed Amir Samir; Ahmed Hussein Elamir; Mohamed Basyouni Helal; Yomna Goudy; Khaled Elbarbary; Mohamed El-Mezayen; Wesam Abo-Elenien; Ebtehal Hashem Abdelazim; Manar Alaa Mabrouk; the ASE-Egypt Group; Kerollos Abdelsayed (BMC Medical Education)
Abstract Background Academic self-efficacy (ASE), influenced by various sociodemographic, lifestyle, and psychological factors, is a critical determinant of academic performance in medical students. In Egypt, the medical education system underwent recent drastic changes. Therefore, we aim to explore the effects of these changes on the variables above and, subsequently, on ASE among a national sample of Egyptian medical students. Methods We conducted a cross-sectional study across 30 Egyptian medical colleges using a validated electronic Arabic survey to evaluate sociodemographic, lifestyle behaviors, psychological factors, and ASE. Categorical variables were described using frequencies and percentages, while Continuous variables were summarized as mean and standard deviation. Bivariate analysis with post-hoc testing, Pearson’s correlation coefficient, and multivariate linear regression were employed to assess the associations between the study variables and ASE. Data analysis was performed using R Statistical Software. Results A total of 1446 participants were included, with a mean age of 20.59 ± 1.68. Of these, 61.5% (n = 890) were Females, while 94.3% (n = 1363) were single. ASE was significantly associated with certain financial status, smoking, sleeping hours, breakfast patterns, diet changes, and fluids. Stress, anxiety, and depression were associated with and correlated to poor ASE. Only depression, oversleeping, and smoking were significant predictors of worse ASE. Conclusions Multiple variables are significantly associated with, correlated to, or predictors of ASE after the recent reform in the Egyptian medical education system. Subsequently, targeted interventions to specific sociodemographic, lifestyle, and psychological factors can be adopted and assessed through future longitudinal pre-post interventional studies.